From Face-to-Face to Digital Learning; Seen from EFL Student's Lenses Enrolled in Online Group Work - Ika Harianingsih; Zailani Jusoh; Ridwan Muhammad Nur (ITScience (Information Technology and Science), 2021)
Numerous higher education institutions around the world must shift their instructions from face-to-face (FTF) to online learning due to Corona Virus Disease in 2019 (Covid19). Furthermore, with the increase in popularity of group work in higher education, especially in the language classroom, and the pivotal changes over the last years, the group works encounter new challenges as they transition to the online world. The study aims to explore the experiences of English as a Foreign Language (EFL) students' engagement in online group works to explore the benefits and challenges in a new learning environment. The qualitative research design provided an in-depth understanding of the students' perceived value of online group work. Further, an interview was used as the main technique in collecting the data from the entire participants. Furthermore, the findings demonstrated that students had generally good attitudes about online group work; however, some students noted that language and communications concerns presented difficulty at times. Nevertheless, the findings also demonstrated that the benefits of this experience surpassed the drawbacks. Thus, the study's findings can be valuable for practitioners and curriculum designers since they highlight the benefits of group work in an online learning setting and the students' problems they may confront during these classes.